Lifeworlds of Baltic Germans : psychography in social context - Fircks, Enno von (Emerald Publishing Limited, 2025)
The present book examines a largely overlooked scientific discipline in Personality Psychology known as Psychography. The origins of Psychography can be traced back to the efforts of William Stern in 1911. As a scientific discipline, Psychography seeks to elucidate how individuals develop significant life patterns throughout their lives and make critical choices regarding their futures. It serves as a qualitative tool for interpreting the complexities of human lives and their transformations within the context of irreversible time. Moreover, this book applies Psychography to concrete examples, particularly focusing on the life and works of the novelist Eduard von Keyserling. Through this analysis, we aim to unravel the experiences of German-Baltic individuals who have had to construct and continually reconstruct their lives in response to the challenges they faced throughout their lifetimes, including war and political turmoil.
Includes index.
Keywords: Germans -- Baltic States -- Psychological aspects.; Psychology -- Social Psychology.; Psychiatry.; Social, group or collective psychology.; elektronické knihy; electronic books